2016
DOI: 10.4238/gmr.15028414
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble RAGE level inversely correlates with left ventricular hypertrophy in essential hypertension patients

et al.

Abstract: ABSTRACT. Soluble receptor for advanced glycation end-products (sRAGE) acts as a decoy to prevent interaction between RAGE and its pro-inflammatory ligands. sRAGE levels have been found to decrease in chronic inflammatory diseases, including hypertension. However, few data have been reported concerning the association between serum sRAGE levels and hypertensive left ventricular hypertrophy (LVH). Fasting blood samples were obtained from 209 essential hypertensive patients, and sRAGE levels were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Systolic pressure increases, while diastolic pressure increases till the age of 50 years after which diastolic pressure decreases. 50 Systolic HTN affects more than 50% individuals older than 60 years of age. Isolated systolic HTN is most common type of HTN among the elderly individuals.…”
Section: Interaction Of Ages With Rage Resulting In Changes In Vasculmentioning
confidence: 99%
“…Systolic pressure increases, while diastolic pressure increases till the age of 50 years after which diastolic pressure decreases. 50 Systolic HTN affects more than 50% individuals older than 60 years of age. Isolated systolic HTN is most common type of HTN among the elderly individuals.…”
Section: Interaction Of Ages With Rage Resulting In Changes In Vasculmentioning
confidence: 99%
“…Previously, sRAGE decreased plasma levels were described in a population of hypertensive patients including severe stages of hypertension [5] and left ventricular hypertrophy (indexed for body surface area) correlated inversely with sRAGE in a group of long-lasting treated hypertensive disease [18]. As confounding factors, the latter study included older patients among the 81 presenting with left ventricular hypertrophy and a large percentage of patients with coronary artery disease [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies on human population have suggested circulating sRAGE as potential biomarker of several pathologies although with conflicting data regarding diabetes and cardiovascular diseases [2932]. Decreased levels of circulating sRAGE or esRAGE have been reported in patients with hypertension [33], metabolic syndrome (MS) [34], in the early phase of type 2 diabetes [35,36] and obesity suggesting sRAGE as an early predictor of cardiovascular risk. Interestingly, sRAGE levels seems to be related to body composition.…”
Section: Introductionmentioning
confidence: 99%